2015
DOI: 10.1115/1.4030166
|View full text |Cite
|
Sign up to set email alerts
|

Multitude of Objectives Based Optimum Designs of Cylindrical Roller Bearings With Evolutionary Methods

Abstract: In the design of cylindrical roller bearings (CRBs), a long life is one of the most essential criteria. However, the life of bearings depends on the multitude of factors that includes the fatigue, lubrication, and thermal characteristics in bearings. In the present work, three primary objectives namely, the dynamic capacity, the elastohydrodynamic lubrication (EHL) minimum film-thickness, and the maximum temperature have been optimized, sequentially. Some of these objectives may be contradicting to each other.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Hence, the bounds for Dm, Z, Dr and le for any CRB are where, subscript LB refers to lower bound and UB refers to upper bound. The remaining design variables KDmin, KDmax, ε, e and β, that create a feasible design space for the bearing design, their bounds have been decided considering the good credibility of results obtained in previous works in the similar fields by considering the same values [25]. The bounds for these variables shall remain the same even in case of robust optimization as the case when they were being used for the deterministic optimization [25], because the variable bounds differ for any CRB for the robust and deterministic optimization only for those variable which have certain tolerances during manufacturing.…”
Section: Variable Boundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the bounds for Dm, Z, Dr and le for any CRB are where, subscript LB refers to lower bound and UB refers to upper bound. The remaining design variables KDmin, KDmax, ε, e and β, that create a feasible design space for the bearing design, their bounds have been decided considering the good credibility of results obtained in previous works in the similar fields by considering the same values [25]. The bounds for these variables shall remain the same even in case of robust optimization as the case when they were being used for the deterministic optimization [25], because the variable bounds differ for any CRB for the robust and deterministic optimization only for those variable which have certain tolerances during manufacturing.…”
Section: Variable Boundsmentioning
confidence: 99%
“…Dragoni [24], while optimizing the dimensions of tapered roller bearings for the maximum static capacity, he found that static capacity varies linearly with-roller infill, square of bearing mean/pitch diameter, ratio of roller length to roller diameter. Tiwari et al [25,26] used the artificial bee colony algorithm for the optimization of rolling bearings. Kim et al [27] enhanced radial and axial stiffness values of an angular contact ball bearing using a micro-genetic algorithm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tiwari and Rahul [15] introduced the thermal based optimization of TRBs using Artificial-Bee-Colony (ABC) using the single objective optimization. Tiwari and Chandran [16] optimized cylindrical roller bearing design using the single-objective optimization by taking the dynamic load rating, the minimum elasto-hydrodynamic film-thickness and the maximum temperature as objective functions. Najjari and Guilbault [17] assessed a modest geometry for cylindrical roller contour.…”
Section: Introductionmentioning
confidence: 99%
“…Tiwari and Chandran 13 optimized three primary objectives namely, the dynamic capacity, the EHL minimum film-thickness, and the maximum temperature in the design of CRBs. Wang et al 14 combined the bearing dynamic analysis and TEHL analysis, and found if the improper axial load is applied for certain bearing speed, the lubrication performance will deteriorate and thermal failure may occur; In addition, the skidding contributes to thermal failure and bad lubrication performance.…”
Section: Introductionmentioning
confidence: 99%